THE SOCIO-ECONOMIC AND POLITICAL SPACE OF RUSSIAN AGGLOMERATION - A. V. Golovin (Современная наука и инновации, 2022)
The socio-economic and political space, represented by urban agglomerations, as a special phenomenon of innovative development, is distinguished by a variety of organizational forms of management, national characteristics and traditions. Based on domestic practice of agglomeration processes, a complex of accumulated problems in this business area is considered. Their elimination will contribute to the formation of a modern model of the spatial organization and development of the country's economy, the achievement of agglomeration effects.